The aquaponic principle—It is all about coupling - Baganz, Gösta F. M.; Junge, Ranka; Portella, Maria C. [UNESP]; Goddek, Simon; Keesman, Karel J.; Baganz, Daniela; Staaks, Georg; Shaw, Christopher; Lohrberg, Frank; Kloas, Werner (Wiley, 2022)
The aquaponic principle is the coupling of animal aquaculture (e.g. fish) with plant production (e.g. vegetables) for saving resources. At present, various definitions of aquaponics exist, some bearing the risk of misinterpretation by dismissing the original meaning or being contradictory. In addition, there is no standard terminology for the aspects of coupling between the aquaponic subsystems. In this study, we addressed both issues. (1) We developed new or revised definitions that are summarised by: Aquaponic farming comprises aquaponics (which couples tank-based animal aquaculture with hydroponics) and trans-aquaponics, which extends aquaponics to tankless aquaculture as well as non-hydroponics plant cultivation methods. Within our conceptual system, the term aquaponics corresponds to the definitions of FAO and EU. (2) A system analysis approach was utilised to explore different aquaponic setups aiming to better describe the way aquaponic subsystems are connected. We introduced the new terms ‘coupling type’ and ‘coupling degree’, where the former qualitatively characterises the water-mediated connections of aquaponic subsystems. A system with on-demand nutrient water supply for the independent operating plant cultivation is an ‘on-demand coupled system’ and we propose to deprecate the counterintuitive term ‘decoupled system’ for this coupling type. The coupling degree comprises a set of parameters to quantitatively determine the coupling's efficiency of internal streams, for example, water and nutrients. This new framework forms a basis for improved communication, provides a uniform metric for comparing aquaponic facilities, and offers criteria for facility optimisation. In future system descriptions, it will simplify evaluation of the coupling's contribution to sustainability of aquaponics.
Keywords: aquaponic farming; aquaponics; coupling degree; coupling type; permanently/on-demand coupled; trans-aquaponics